Care and development of the dairy cow - Bainer, Harry M. (My University, 1900)
Introduction: To make a good dairy cow, start with the calf. Choose the calf from the best cow, and raise it with purpose in view that it is to be a better cow than its mother. The young cow that is not better than its mother has not been raised right. Naturally, all calves of a herd are treated about the same, the dairy calf gets the same care as the beef calf, or on the other hand, the beef calf is treated just like the dairy calf. This is a mistake. In raising a beef calf, meat is the object, and the quicker that a pound of meat can be put on, the cheaper it will be. In raising the dairy calf, she must be kept in a good growing condition. There must not be an accumulation of fat; for muscle, bone, and a good constitution, coupled with strong digestion are what is wanted in the dairy cow. The difference in treatment should be more marked at the age of 12 to 18 months than before, as flesh is more rapidly accumulated at that time, and is more likely to injure her as a dairy heifer. As has been shown at the Iowa Experiment Station, and elsewhere, the heifer shows a little greater tendency to easy fattening and early maturity than the steer under the same conditions, therefore, the treatment of the two must be different. Excessive development of the flesh-forming function almost always takes place at the expense of the milk production. A liberal amount of bulky feed should be given to the heifer, to stimulate the growth of a roomy digestive tract. The good dairy cow must be able to digest a large amount of food, that she may produce accordingly. She must have plenty of lung capacity, in order to purify the large amount of blood that is necessary in the digestion of her food and in the secretion of milk. She may be considered as a machine into which we can safely feed our corn and alfalfa, and have them converted into milk and butter.
Citation: Bainer, Harry M. Care and development of the dairy cow. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Dairy Cows; Animal Husbandry; Theses